Prevalence of Depression and Its Associated Factors among Orphan Children in Orphanages in Ilu Abba Bor Zone, South West Ethiopia - Shiferaw, Gemechu (Psychiatry J, 2018)
INTRODUCTION: Orphans are the special group of children who are generally deprived and prone to develop psychiatric disorders even those reared in well-run institutions. These children and adolescents living as orphans or in stigmatized environments are vulnerable because of the loss of parent figures. The HIV/AIDS epidemic has contributed to a drastic increase in the number of orphans and vulnerable children and other causes in sub-Saharan Africa. However, little is known about the prevalence of depression and associated factors among orphanage children in areas such as Ethiopia. OBJECTIVE: The aim of this study was to assess the prevalence of depression and its associated factors among orphans in Ilu Abba Bor Zone orphanages, 2016. METHODS: An institutional based cross-sectional study was conducted among orphan children in orphanages at Mettu and Gore. A total of 220 orphans were included from the two orphanages and make the response rate of 98.2%. Pretested semistructured questionnaire was used for interviewing the study participants. The collected data were coded, entered into EPI-INFO 7.0. Software, and exported to SPSS version 20 for statistical analysis. The strength of association between variables was assessed using crude and Adjusted Odds Ratio by running logistic regression and the cut-off point for declaring statistical significance was P- value <0.05 or 95% confidence interval which does not contain the null value. RESULTS: A total of 216 orphan children were interviewed with response rate of 98.2%. The overall prevalence of depression was 24.1%. The mean age of participants was 14.2 years ± 9.90 SDs and range from 11 to 17 years. Sex [Adjusted Odds Ratio = 3.29, 95% CI (1.41, 7.46)]; age [Adjusted Odds Ratio=2.09,95% CI (3.7; 5.01)]; duration of stay in foster care [Adjusted Odds Ratio= 2.08 (1.01; 8.33)]; previous physical abuse [Adjusted Odds Ratio= 3.1 (2.1; 5.06)]; having medical illness [Adjusted Odds Ratio=1.94,95% CI (2.01;3.56)]; orphan status [Adjusted Odds Ratio=2.5,95% CI (1.62; 3.56)]; and suicidal tendency [Adjusted Odds Ratio= 4.8 (3.41; 9.03)] were independent predictors of depression among orphans in orphanages. CONCLUSION AND RECOMMENDATIONS: Prevalence of depression was high among orphans and this finding suggests that screening for depression and mental and psychological care should be integrated into routine health care provided to orphans and that there is a further need to establish preventive measures against depression.